The prevalence and associated occupational risk factors of lower back pain among registered nurses at Tygerberg Hospital, South Africa : a cross-sectional study - Tafaune, Geoffrey (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2022.